Coherent Anti-Stokes Raman Scattering Microscopy and Its Applications - Li, Shaowei; Li, Yanping; Yi, Rongxing; Liu, Liwei; Qu, Junle (Frontiers in Physics, 2020)
Coherent anti-Stokes Raman scattering (CARS) microscopy can provide high resolution, high speed, high sensitivity, and non-invasive imaging of specific biomolecules without labeling. In this review, we first introduce the principle of CARS microscopy, and then discuss its configuration, including that of the laser source and the multiplex CARS system. Finally, we introduce the applications of CARS in biomedicine and materials, and its future prospects.